(untitled) (Latakia University Journal -Biological Sciences Series, 2024)
In this study, four fish were caught from the water of Ibn Hani area in Latakia city using a metal cage at a depth of 8 meters in a rocky bottom on 3/2/2024. The fish were transferred to the Marine Biology Laboratory at the Higher Institute for Marine Research. Morphometric measurements were carried out on a fresh fish individual, fin equations were calculated, and the species was classified according to international taxonomic references. The results showed that the individual fish belongs to the Centrolophidae family and bears the name Schedophilus ovalis and is recorded for the first time in Syrian marine waters.